How do students self-regulate in an online math learning context? A multiple-case study - Castillo, John Christopher Dimasaka (Animo Repository, 2023)
Mathematics learning is an educational goal crucial for its role in supporting learning in other math-based and non-math learning areas. During the pandemic, mathematics learning became even more daunting for learners, who had to very quickly shift to online learning - a modality that demands very high levels of autonomy, monitoring, and control of cognition, affect, and behavior. Using a multiple case study approach, this study examined how students self-regulate in an online math learning context among ten highly self-regulated learners who were enrolled in engineering programs in a university in Manila. Content and thematic analyses of multiple semi-structured interviews and weekly diary entries collected longitudinally through eleven (11) weeks of a fully online Integral Calculus class elucidated three phases of online math task performance: pre-performance, performance, and post-performance. During pre-performance, precursors of OSRL were found to have direct impacts on students’ deployment of OSRL strategies: perceptions about the task, performance-related emotions, circumstances surrounding performance, and learning goals. These precursors inform the use of metacognitive strategies and task strategies during the performance phase, which were the two most often deployed and effective strategies in assisting students to concretize their online math learning goals. When the tasks and circumstances become overwhelming and intimidating, students use further contingency strategies. Levels of happiness, motivation, and satisfaction which were documented through ten weeks of journal reflection were instructive of the outcomes of effortful and successful OSRL. Finally, a task-based model of OSRL in online math learning was developed, explaining the intricate nuances of OSRL vis-à-vis nature of online math tasks. Implications for further improving empirical knowledge on online self-regulated learning in math are discussed. Keywords: mathematics learning, online self-regulated learning, online math learning, mathematics education